EFFECT OF FISH-OIL-ENRICHED INTRAVENOUS LIPID EMULSION ON SYSTEMIC INFLAMMATORY RESPONSE SYNDROME IN POST INTESTINAL SURGERY CHILDREN - Khadijah Rizky Sumitro; Meta Herdiana Hanindita; Nur Aisiyah Widjaja; Roedi Irawan (Universitas Airlangga, 2020)
Intravenous lipid emulsions (IVLE) is one of the compositions of the parenteral nutrition (PN) that recommended in children who cannot meet their caloric requirements especially after small intestinal surgery and diff erentiated by their infl ammatory eff ects. The fi rst generation IVLE is proinfl ammatory, the second and the third are infl ammatory neutral, while the fourth (fi sh-oil-enriched) is anti-infl ammatory. The objective of this study is to investigate the eff ect of fi shoil enriched IVLE on systemic infl ammatory response syndrome (SIRS) in children after small intestinal surgery. A retrospective study using medical record was undertaken in children after small intestinal surgery admitted Dr. Soetomo Hospital, Surabaya in 2016-2017. Children with duodenal and jejunoileal atresia who had PN for at least three days were included. The types of IVLE used are FOLE and non-FOLE. Defi nition of SIRS was based on International Pediatric Sepsis Consensus Conference in 2005. A total of 25 children were included in this study. There were 44% children received FOLE and 48% received non-FOLE while 8% children received no IVLE. Median duration and dose of IVLE was 8 (5-15,5) days and 1,8 (1,25-2) g/kg/day. SIRS was signifi cantly more common in girls (OR 9 95%CI 1,3-63,0; p=0,036) and in the non-FOLE children (OR 8,0 95% CI 1,24 – 51,50; p=0,022).